ANALISIS FLEKSIBILITAS KERJA DAN LINGKUNGAN NON FISIK TERHADAP KEPUASAN KARYAWAN MARKETING PT ASTRA HONDA MOTOR - Yuwan Apriliandi; Nor Norisanti; Resa Nurmala (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to determine the effect of work flexibility and non-physical environment on employee satisfaction. The method used in this research is a quantitative research method with a descriptive and associative approach. Data collection techniques use questionnaires and literature studies. The population in this study consisted of 31 Honda Motor sales people in Sukabumi, and all members of the population were used as samples. The data analysis technique used is the classic assumption test, multiple linear regression analysis which includes the coefficient of determination, multiple correlation coefficient and partial test (t test). The research results show that the majority of respondents feel they have a high level of work flexibility, a very good work environment, and an adequate level of job satisfaction. Statistical analysis states that work flexibility has a positive and significant influence on job satisfaction, and a good work environment also has a positive and significant influence on job satisfaction. The conclusion that can be drawn from this research is that work flexibility and the non-physical environment play an important role in increasing employee satisfaction. Findings show that employees tend to feel satisfied with their jobs when they have a high level of flexibility and a good work environment.